Role and psychological dependenci arrangement of opioid by type of reseptor opioid - Arif Nurrochmad, Arif Nurrochmad (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Opioid receptor can be classified as p., 8, and K-opioid receptor that widely expressed in the CNS. The development of selective receptor agonist and cloning of each receptor have contributed greatly to our increasing knowledge of the neuropharmacological profile of each opioid receptor type. This review focuses on the functional interaction among these opioid receptor types that contribute to opioid dependence especially in psychological dependence. Several lines of evidence provide arguments to support substantial roles for p-opioid receptors and the possible involvement of 8-opioid receptors in the development of physical and psychological dependence on morphine. Many studies have pointed to the mesolimbic dopaminergic system projecting from the ventral tegmental area to the nucleus accumbens as a critical site for the initiation of psychological dependence on opioids. It is important to note as the broad existence of opposing interaction between p/8-, and K-receptors in the central nervous system. The activation of Kopioid receptors leads to the suppression of unpleasant p.- or 8-mediated side effects such as withdrawal and rewarding effect. Considering the functional interaction among opioid receptor types, the co-administration of morphine-like compounds with K-receptor agonists lead suppressing the side effects of p-opioid receptor agonist that benefit for the pain management.Key words: Opioid receptor - receptor types - psychological dependence - morphine